Single and combined toxic effects of clarithromycin and levofloxacin on Microcystis aeruginosa. Issue 1 (31st December 2022) - Wu, Yixiao; Ding, Huijun; Wan, Liang; Zhang, Weihao; Zhang, Yan; Yang, Lin; Zhao, Chong
ABSTRACT: This study compared the single and joint toxic effects of clarithromycin (CLA) and levofloxacin (LEV) on Microcystis aeruginosa . CLA was more toxic to algae than LEV, and the 96h-EC50 s were 43.31 and 437.6 µg/L, respectively. The synergetic interaction of two antibiotics was detected. This synergetic action was also observed on Fv/Fm, chlorophyll a, and phycobiliprotein. The increase in reactive oxygen species (ROS) and malonaldehyde demonstrated that antibiotic exposure caused severe oxidative stress, which can destroy the membrane system, hinder photosynthesis and finally inhibit cell growth. The antioxidant enzyme activities were improved significantly, especially in the joint exposure treatment, which indicates that the antioxidant defense system can be activated to scavenge ROS. The release of microcystins (MCs) was accelerated under single or combined antibiotic exposure. The promotion of MCs discharge from cyanobacteria caused by the co-occurrence of CLA and LEV in water environment may pose a severe ecological risk to ecosystem.